(untitled) (Research, Society and Development, 2022)
Leprosy is a chronic infection caused by Mycobacterium leprae. A curable infectious disease remains endemic in more than 140 countries around the world. The objective of this study was to describe the epidemiological profile of the population diagnosed with leprosy in the State of Acre, Brazil, from 2018 to 2022. This is a retrospective study, using secondary data collected at the Department of Informatics from SUS – DATASUS and tabulated from TABNET. There were 520 cases of the disease in the state during the study period, most of them male (65.6%) and (85.2%) of mixed race/skin color. The most affected age group was 15 years old and over (94.8%) and there were 27 cases in children under 15 years old (5.2%). The most prevalent clinical form was borderline (62.5%) and the most frequent outcome was cure (58.5%). It is essential that health education interventions be constantly carried out for the population, in addition to intensifying the active search, individualized and direct assistance, and the examination of contacts of leprosy patients, in an attempt to reduce or eliminate cases of the disease.